2011
DOI: 10.1074/jbc.m110.176685
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-dependent Proteasomal Degradation of Human Liver Cytochrome P450 2E1

Abstract: Human liver CYP2E1 is a monotopic, endoplasmic reticulumanchored cytochrome P450 responsible for the biotransformation of clinically relevant drugs, low molecular weight xenobiotics, carcinogens, and endogenous ketones. CYP2E1 substrate complexation converts it into a stable slow-turnover species degraded largely via autophagic lysosomal degradation. Substrate decomplexation/withdrawal results in a fast turnover CYP2E1 species, putatively generated through its futile oxidative cycling, that incurs endoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 94 publications
(107 reference statements)
2
41
0
Order By: Relevance
“…Our own LC-MS/MS analyses of in vitro phosphorylated human liver CYP2E1 peptide digests further revealed that Ser129 is a major (>98%) PKA-phosphorylation site both in the native and CuOOH-inactivated proteins (Wang et al, 2011). This residue is also correspondingly phosphorylated by PKC to >23% and 32%, respectively (Wang et al, 2011). However, the advent of much more sensitive LC-MS/MS methodology has led to the recognition that Ser129 is but one of 16 different CYP2E1 S/T-residues that are phosphorylated.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our own LC-MS/MS analyses of in vitro phosphorylated human liver CYP2E1 peptide digests further revealed that Ser129 is a major (>98%) PKA-phosphorylation site both in the native and CuOOH-inactivated proteins (Wang et al, 2011). This residue is also correspondingly phosphorylated by PKC to >23% and 32%, respectively (Wang et al, 2011). However, the advent of much more sensitive LC-MS/MS methodology has led to the recognition that Ser129 is but one of 16 different CYP2E1 S/T-residues that are phosphorylated.…”
Section: Introductionmentioning
confidence: 88%
“…Thus, although all CYPs 3A as well as all structurally/functionally inactivated P450s are predominantly ERAD/UPD targets (Correia et al 1987, 1992a, 1992b, 2005; Correia, 2003; Tierney et al, 1992; Sohn et al, 1991; Dai & Cederbaum, 1995; Roberts, 1997; Schmiedlin-Ren, 1997; Korsmeyer et al, 1997; Wang et al, 1999; Murray & Correia, 2001; Morishima et al, 2005; Liao et al, 2006; Correia & Liao, 2007; Faouzi et al, 2007; Lee et al, 2008), native P450s such as rat liver CYPs 2B1 and 2C11 are predominantly ERAD-II substrates requiring ALD instead of UPD, henceforth referred to as the ERAD/ALD pathway (Masaki et al, 1987; Ronis & Ingelman-Sundberg, 1989; Ronis et al, 1991; Murray et al, 2002; Liao et al, 2005). On the other hand, human or rat liver CYP2E1 utilizes both ERAD/UPD and ERAD/ALD pathways, depending on whether it is suicidally inactivated or native/substrate-free, or native/substrate-bound, respectively (Song et al, 1989; Roberts et al, 1995; Bardag-Gorce, 2002; Morishima et al, 2005; Wang et al, 2011). Thus, although a preferential P450 routing into either pathway apparently exists, the pathway not chosen may simply represent a convenient alternative backup, in eventualities such as ER-stress when ERAD/UPD is overloaded and clogged with misfolded/aggregated proteins awaiting clearance, and competition for the ERAD/UPD cellular machinery is insurmountable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein phosphorylation has been linked both to activation (41) and to inhibition (42,43) of proteasome-mediated degradation of the target protein. One of the questions of the current study was to address if CK2-mediated phosphorylation affects degradation of CP via the CPIP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Protein ubiquitination is a pathway for a variety of ­proteins and plays a critical role in post-translational modification [35]. Previous studies have suggested that CYP2E1 protein contains 37 lysyl residues, which could be considered a candidate for ubiquitin conjugation, and there are likely 2 subtypes of ubiquitination systems involved in the degradation of the free CYP2E1 [36]. Therefore, the difference between mRNA and ­protein level may have been partly expanded, although only scarce information on ubiquitin-mediated CYP450 family degradation is currently available.…”
Section: Discussionmentioning
confidence: 99%